Tuturan Imperatif dalam Acara Indonesia Lawyers Club pada Bulan Agustus 2020 - Deva Asriyuli; Ermawati Sulaiman (UIR Press, 2022)
ABSTRACT This study examines imperative speech politeness in the Indonesia Lawyers Club event in August 2020. The problems in this study are: (1) What are the types of imperative speech in the Indonesia Lawyers Club event in August 2020. (2) What are the maxims of politeness principles in each imperative speech? in the Indonesia Lawyers Club event in August 2020. This study aims to (1) describe, analyze, interpret, and conclude the types of imperative speech in the Indonesia Lawyers Club event in August 2020. (2) Describe, analyze, interpret, and conclude the maxims the principle of politeness in every imperative speech at the Indonesia Lawyers Club event in August 2020. The approach that the author uses in this study is a qualitative approach. The method used in this research is descriptive method. Data collection techniques used by the author in order to collect data, namely by using documentation, listening and note-taking techniques. As a reference, the author uses the theory proposed by Rahardi (2005:50). Types of imperative speech in the Indonesia Lawyers Club event in August 2020 the authors found 50 imperative speeches, including, 12 ordinary imperative speeches, 8 request imperative utterances, 11 permission imperative utterances, 11 invitation imperative utterances and 8 orders imperative utterances. The maxim of politeness principles contained in every imperative utterance at the Indonesia Lawyers Club event in August 2020 the authors found 22 imperative utterances containing the maxims of politeness principles, including, 11 maxims of wisdom, 4 maxims of generosity, 2 maxims of appreciation, 4 maxims of consensus and 1 maxim sympathy maxim of sympathy used in imperative sentences spoken by the teacher amounted to 2 speech data.